Evidence and emerging trends in local therapy for metastatic hormone-sensitive prostate cancer: a narrative review - Brönimann, Stephan; Singla, Nirmish; Korn, Stephan M; Huebner, Nicolai A; Shariat, Shahrokh F (Memo, 2024)
INTRODUCTION: Metastatic hormone-sensitive prostate cancer (mHSPC) displays both simultaneous and sequential patterns of metastasis, emphasizing a comprehensive treatment approach that integrates both local therapy and systemic treatment strategies. The increasing use of molecular imaging has led to a rise in mHSPC diagnoses, underscoring the importance of identifying the right patient population and effective treatment concepts for this disease state. RESULTS: Two prospective trials, HORRAD and STAMP EDE, investigated prostate radiotherapy (RT) for mHSPC; however, they did not show an overall survival (OS) benefit in the unselected cohort. Nonetheless, RT showed favorable outcomes in patients with fewer than five bone metastases, resulting in a 7% 3-year survival improvement and supporting the integration of RT in multimodal treatment for men with oligometastatic mHSPC. Regarding cytoreductive prostatectomy (cRP), the TRoMbone Trial confirmed its feasibility and safety. In addition, findings from the FUSCC-OMPCa Trial demonstrated improved 3-year radiographic progression-free survival and OS rates with acceptable rates of complications and incontinence. Recent data from the LoMP registry have further supported superior OS and cancer-specific survival (CSS) in patients undergoing cRP compared to systemic therapy alone. Notably, no significant differences in OS and CSS were observed between the cRP and RT groups. However, cRP-treated patients exhibited superior 2-year local event-free survival when compared to those treated with RT. CONCLUSION: RT in combination with systemic therapy remains the established first-line treatment for low-burden mHSPC, though the exact definition of low metastatic burden remains contentious. Precise assessment of metastatic burden is vital to identify patients who would derive the greatest benefit from RT. As treatment paradigms evolve, embracing multimodal approaches holds potential for optimizing outcomes in patients with mHSPC. Further research is needed to solidify the role of cRP as a standard therapeutic approach and to refine treatment strategies for improved patient outcomes.